Surgical management of superior petrosal sinus dural arteriovenous fistulae with dominant internal carotid artery supply. Issue 3 (June 2018) - Stapleton, Christopher J; Patel, Anoop P; Walcott, Brian P; Torok, Collin M; Koch, Matthew J; Leslie-Mazwi, Thabele M; Rabinov, James D; Butler, William E; Patel, Aman B
Background: While technological advances have improved the efficacy of endovascular techniques for tentorial dural arteriovenous fistulae (DAVF), superior petrosal sinus (SPS) DAVF with dominant internal carotid artery (ICA) supply frequently require surgical intervention to achieve a definitive cure. Methods: To compare the angiographic and clinical outcomes of endovascular and surgical interventions in patients with SPS DAVF, the records of all patients with tentorial DAVF from August 2010 to November 2015 were reviewed. Results: Within this cohort, eight patients with nine SPS DAVF were eligible for evaluation. Five DAVF were initially treated with endovascular embolization, while four underwent surgical occlusion without embolization. Of the SPS DAVF treated with embolization, two (40%) remained occluded on follow-up, while the remaining three (60%) persisted/recurred and required surgical intervention for definitive closure. Of the four SPS DAVF treated with primary surgical occlusion, all four (100%) remained closed on follow-up. In addition, of the three SPS DAVF that persisted/recurred following embolization and required subsequent surgical closure, all three (100%) remained occluded on follow-up. Two (100%) SPS DAVF that were successfully treated with embolization had major or minor external carotid artery supply, while the three (100%) persistent lesions had major ICA supply via the meningohypophyseal trunk (MHT). Three (75%) of the four SPS DAVF treated with primary surgical occlusion had dominant MHT supply. Conclusion: Complete endovascular closure of SPS DAVF with dominant ICA supply via the MHT may be difficult to achieve, while upfront surgical intervention is associated with a high rate of complete occlusion.